Compensatory training sessions, do they really compensate? - Casamichana, D.; Barba, E.; Aguirre, G.; Agirrezabalaga, O.; Castellano, J. (International Journal of Sports Science & Coaching, 2025)
The aim of this study was to compare the external load accumulated by players belonging to three teams of the same professional club in the compensatory training session, training the day after the match, expressing this both in absolute values and in values relative to the match demands. Fifty-one soccer players from three different categories (professional team [PRO] n= 16 players; reserve team [RES]= 15 players; and second reserve team [RES2]= 20 players) were monitored by micro-electromechanical systems devices in compensatory training sessions. Large and very large differences between teams were shown in the variables most related to volume (duration, player load, total distance, acceleration load and distance at >14 km h-1), while the variables most related to intensity show trivial and small differences between teams (distance at >21 and >24 km h-1, and number of accelerations and decelerations). Our main finding agreed with our hypothesis, showing that most of the external load variables range between 30-90% of the official match load, most of the external load variables being in ranges close to 50-60% of the match demands, reaching a higher percentage in the variables related to the accelerations and decelerations actions.